Genomic Variation Influences Methanothermococcus Fitness in Marine Hydrothermal Systems - Hoffert, Michael; Anderson, Rika E.; Reveillaud, Julie; Murphy, Leslie G.; Stepanauskas, Ramunas; Huber, Julie A. (Frontiers in Microbiology, 2021)
Hydrogenotrophic methanogens are ubiquitous chemoautotrophic archaea inhabiting globally distributed deep-sea hydrothermal vent ecosystems and associated subseafloor niches within the rocky subseafloor, yet little is known about how they adapt and diversify in these habitats. To determine genomic variation and selection pressure within methanogenic populations at vents, we examined five Methanothermococcus single cell amplified genomes (SAGs) in conjunction with 15 metagenomes and 10 metatranscriptomes from venting fluids at two geochemically distinct hydrothermal vent fields on the Mid-Cayman Rise in the Caribbean Sea. We observed that some Methanothermococcus lineages and their transcripts were more abundant than others in individual vent sites, indicating differential fitness among lineages. The relative abundances of lineages represented by SAGs in each of the samples matched phylogenetic relationships based on single-copy universal genes, and genes related to nitrogen fixation and the CRISPR/Cas immune system were among those differentiating the clades. Lineages possessing these genes were less abundant than those missing that genomic region. Overall, patterns in nucleotide variation indicated that the population dynamics of Methanothermococcus were not governed by clonal expansions or selective sweeps, at least in the habitats and sampling times included in this study. Together, our results show that although specific lineages of Methanothermococcus co-exist in these habitats, some outcompete others, and possession of accessory metabolic functions does not necessarily provide a fitness advantage in these habitats in all conditions. This work highlights the power of combining single-cell, metagenomic, and metatranscriptomic datasets to determine how evolution shapes microbial abundance and diversity in hydrothermal vent ecosystems.